PENDIDIKAN DAN POLITIKUS : ANALISIS PEMIKIRAN M. NATSIR TENTANG PENDIDIKAN ISLAM DI INDONESIA - Ahmad Hayati Nufus (IAIN Ambon, 2018)
Abstract: This paper aims to analyze the thoughts of Mohammad Natsir on Islamic Education of Indonesia. Indeed education is a shared responsibility of all people, not just the task of education experts, political experts can play an active role in education. Long before independence and after independence education became the first and foremost thing that must be considered and realized according to the culture and needs of the people of Indonesia. Mohammad Natsir is one of the Indonesian politicians who are able to bring education changes and education curriculum in Indonesia. He no longer sees that public and religious education are separated and unrelated, but integrated. This is evidenced by the existence of educational institutions that he pioneered the Islamic education school and some educational thinking that until now still used in the education curriculum of the Ministry of Religious Affairs of the Republic of Indonesia with the term